The pathology of “Judicial Justice” in the Middle East and Its correction mechanism - Ghasemi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Social justice has been described in various areas, one of the most important of these areas is the realization of judicial justice. Democratic and democratic governments, based on the will and opinion of the people, are formed and run in pursuit of the implementation of judicial justice as one of the essential means for the realization of social justice in society. The Islamic Republic of Iran, as a democratic and religious system, has pursued justice since its inception. Now and after four decades of the Islamic Revolution, the pathology of the realization of social justice in the judicial field is essential. Therefore, this paper seeks to achieve judicial justice in the field of judging and judging and dealing with opponents and criminals, and addresses the problems and solutions to these problems. Based on the findings of this study, the status of the performance of the system in the field of the realization of judicial justice reveals that the most important problems and injuries are in the way of judging, the process of prosecution, the type of dealing with people and financial corruption, and the basic solution of its exit, transparency, supervision and Changes in the judicial system. This research is a descriptive-analytical method that describes the damages of the realization of judicial justice and its correction mechanism.